DIVORCE AND ITS CONSEQUENCES - Lazizakhon Ikramova (Scholar Express Journal, 2022)
The article discusses divorces and their problems, which have been more relevant than ever for several decades. Every year the number of divorces is inexorably growing, and the number of couples entering into a legal marriage, on the contrary, is decreasing. Almost half of the men and women who have married, in the future, get divorced. The consequences of this situation are reflected both on the subsequent life of the spouses already out of wedlock, and on modern society. The level of responsibility of the population is decreasing, the number of single-parent families is growing.
Keywords: Divorce; Emotional Condition; Positive Affect; Negative Affect